Influence of phase formation processes in lithium zirconate ceramics on strength and thermal properties - Kozlovskiy, L.A.; Abyshev, B.; Zhumadilov, K.Zh.; Shlimas, D.I. (KU Publ., 2022)
The article is devoted to the study of the properties of lithium zirconate ceramics obtained by solid-phase synthesis. The choice of lithium zirconate ceramics as objects of study is due to the great prospects for their use as materials for tritium propagation. Results of a study of the influence of the LiO/ZrO2/Li2ZrO3 → LiO/Li2ZrO3 → Li2ZrO3 type phase transformations in ceramics, depending on the annealing temperature, on the strength and thermophysical parameters of ceramics are obtained. During the studies, it was found that the change in hardness and crack resistance are directly dependent on the phase composition and concentration of impurity phases in the composition of ceramics. It has been determined that the displacement of lithium oxide and zirconium dioxide impurity phases leads to an increase in hardness and an increase in resistance to cracking under single compression. It has been established that at annealing temperatures above 900°C, the change in strength and thermophysical parameters is minimal. At the same time, a change in the phase composition of the LiO/ZrO2/Li2ZrO3 → Li2ZrO3 type ceramics leads to an increase in the thermal conductivity coefficient by (15- 20)%.
Keywords: lithium-containing ceramics; phase transformations; hardness; thermal conductivity; nuclear materials